Water turbidity-induced alterations in coloration and courtship behavior of male guppies (Poecilia reticulata) - Camargo-dos-Santos, Bruno [UNESP]; Goncalves, Bruno Bastos; Bellot, Marina Sanson [UNESP]; Guermandi, Isabela Inforzato [UNESP]; Barki, Assaf; Giaquinto, Percilia Cardoso [UNESP] (Springer, 2021)
Water turbidity deteriorates visibility and thereby may change the physiology and behavior of aquatic animals that rely on vision. In the guppy fish (Poecilia reticulata), a key element in the mating behavior and reproductive success of males is female mate choice, which is predominantly based on visual signals. Females choose attractive males based on body coloration, and males court females by displaying their coloration. Here, we demonstrate that guppy males exhibit morphological and behavioral adjustments in response to changes in the visual environment. Males reared in turbid water had more conspicuous coloration than males reared in clear water, with higher intensity of carotenoid-based and ultraviolet colors, but not a larger area of red spots on the body. However, they performed less courtship displays in turbid water than males reared in clear water performed in clear water. Thus, increased coloration in turbid-water males was not accompanied by increased effort to display it. Although our findings demonstrated developmental plasticity in mating-related traits, turbidity-induced alteration in coloration did not match behavior change as could be predicted by favoring male attractiveness.
Keywords: Conspicuousness; Courtship display; Developmental plasticity; Ultraviolet coloration; Carotenoid-based coloration